2022
DOI: 10.7150/ijbs.68990
|View full text |Cite
|
Sign up to set email alerts
|

IL-6/STAT3 Axis Activates Glut5 to Regulate Fructose Metabolism and Tumorigenesis

Abstract: Cancer cells frequently use fructose as an alternative energy and carbon source, to fuel glycolysis and support the synthesis of various biomacromolecules. Glut5 is the only fructose-specific transporter, which lacks the ability to transport other carbohydrates such as glucose and galactose. Interplay between inflammatory factors and cancer cells renders inflammatory tissue environment as a predisposing condition for cancer development. Nevertheless, how inflammatory factors coordinate with fructose metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Combining Tagln knockdown with TAGLN mutants might help to detect phenotypic changes that could provide some mechanistic insights. Secondly, in the present study, we focused on IL-6 as it is a key inflammatory cytokine involved in different types of cancer [58][59][60][61][62]. However, it remains unexplored whether the same observations would occur for other cytokines.…”
Section: Discussionmentioning
confidence: 95%
“…Combining Tagln knockdown with TAGLN mutants might help to detect phenotypic changes that could provide some mechanistic insights. Secondly, in the present study, we focused on IL-6 as it is a key inflammatory cytokine involved in different types of cancer [58][59][60][61][62]. However, it remains unexplored whether the same observations would occur for other cytokines.…”
Section: Discussionmentioning
confidence: 95%
“…Huang and colleagues reported that pro-inflammatory signaling, triggered by IL-6, could facilitated the uptake and utilization of fructose in the DU145 PCa cell line. 84 The authors found a dynamic increase in the expression of Glut-5, both at the protein and mRNA levels, following IL-6 exposure, which was associated with the binding of STAT3 to the SLC2A5 promoter region. Activated STAT3 correlates with aggressive PCa, high Gleason score, regulation of drug resistance, and reactivation of androgen receptor (AR) in castration-resistant prostate cancer (CRPC) progression.…”
Section: Fructose-glut-5 Relationship In Prostate Tumor Progression A...mentioning
confidence: 96%
“…The molecular regulation of the Glut‐5 transporter in benign and malignant human prostate cells has not been fully elucidated; however, inflammatory signaling has been implicated. Huang and colleagues reported that pro‐inflammatory signaling, triggered by IL‐6, could facilitated the uptake and utilization of fructose in the DU145 PCa cell line 84 . The authors found a dynamic increase in the expression of Glut‐5, both at the protein and mRNA levels, following IL‐6 exposure, which was associated with the binding of STAT3 to the SLC2A5 promoter region.…”
Section: Fructose–glut‐5 Relationship In Prostate Tumor Progression A...mentioning
confidence: 99%
“…have shown that STAT6 is implicated in regulating the transcription in GLUT5 in a PC cell line (ex. DU145) ( 57 ), yet this remains to be characterized in other types of cancers. Secondly, how fructolytic enzymes can contribute to the pro-survival benefits of cancer cells, independent of their classical roles in metabolism, is only beginning to be appreciated, such as the secondary roles of KHK-A observed in BC ( 45 ) and HCC ( 38 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%